2016
DOI: 10.1111/vec.12507
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating the use of cervical ultrasound to confirm endotracheal intubation in dogs

Abstract: Cervical ultrasound has high sensitivity and moderate specificity for ET intubation, and may be a useful tool to confirm ET intubation in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…), whereas a right lateral transverse intercostal approach or a suprailiac location has recently been reported in dogs (Herreria‐Bustillo et al . , Meneghini et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), whereas a right lateral transverse intercostal approach or a suprailiac location has recently been reported in dogs (Herreria‐Bustillo et al . , Meneghini et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few veterinary studies on CVC measurements at different location have been published (Herreria‐Bustillo et al . , Meneghini et al . ), none has evaluated the inter‐ or intra‐operator variability of their procedure.…”
Section: Introductionmentioning
confidence: 99%
“…First, capnographs can be expensive and not ubiquitously present in veterinary emergency rooms or even in operating rooms. Secondly, when cardiac output is extremely low—or even zero during cardiac arrest—CO 2 may be undetectable even if the tube is correctly placed ( Gottlieb et al, 2020 ; Herreria-Bustillo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although described decades ago ( Raphael & Conard III, 1987 ), just recently ultrasound (US) has emerged as an alternative to confirm ET intubation in veterinary medicine ( Herreria-Bustillo et al, 2016 ). Studies in humans have shown promising results, demonstrating high accuracy for the method and a fast learning curve ( Chenkin et al, 2015 ; Chou et al, 2011 ; Liu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation